Penentuan Titik Lokasi Stasiun Dan Rute Jaringan Jalur Sepeda Bike-sharing dalam Mendukung Mobilitas Wisatawan di Kawasan Pantai Barat dan Timur Pangandaran - Nurrizkyta, Ditha; Juansyah Abdulrahman, Yopi; Willy Anto, Bima (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2024)
Pangandaran one of the leading area in West Java which known famous for it’s natural beauty coastal scenary. Tourist favorite destinations in Pangandaran are West And East Coast Beach Pangandaran. They often travel to Pangandaran for holiday using private vehicles which can cause traffic congestion, especially during peak season. Therefore, bike-sharing system can make a new alternative mobility option. The most important thing in managing bike-sharing system is to plan optimal location bike-sharing station and determine bicycle lane route. Data collection techniques used primary data, consist of AHP methode and road inventory survey, while secondary data used road network, land use, terminal distribution and bus stop maps. The analysis technique used is SMCA (Spatial Multicriteria Analysis) to determine the potential location of bike-sharing stations and analysis of determining bicycle lane routes by considering the technical guidelines in bicycle lane planning, road conditions from road inventory surveys, and potential location points of bike-sharing stations. The purpose of this research is to know which areas in West and East Coast Pangandaran are potential for planning bike-sharing stations and route bicycle lane. Based on the results SMCA, seven potential locations of bike-sharing stations was proposed and for bicycle lane route, eight road sections selected with the various considerations from the techinal requirements, but some of the existing road sections need to re-design with recommendations for road geometric conditions and traffic engineering so that the technical requirements meet the minimum road width for bicycle activity as mention in technical guidelines for bicycle lane planning.